Strengthening the Profile of Pancasila Students through the Development of Mathematical Logic E-Books Integrated with Moral Value: Penguatan Profil Pelajar Pancasila Melalui E-Book Logika Matematika Terintegrasi Nilai Akhlak - Nihayati, Nihayati; Astuti, Robia; Sutriningsih, Naning; Pasha, M Kemal; Feliza, Destri Anggita; Gunawan, Dadang (Universitas Muhammadiyah Sidoarjo, 2024)
Moral decadence in students requires character strengthening to form the nation's generation by the goals of national education as stated in the 2003 National Education System Law. The formation of student's character can be realized through strengthening the Pancasila student profile in a learning process. The use of learning media that is interactive and integrated with moral values ​​is one of the efforts to realize the Pancasila student profile. So this research aims to produce a mathematical logic E-Book that is feasible and effective for use in the learning process to support strengthening the profile of Pancasila students. This type of research is R&D (Research and Development) development research which refers to the ADDIE development model. The subjects in this research were class XII students at Pringsewu Muhammadiyah High School. The data analysis techniques used are feasibility tests based on material expert assessments, learning design expert assessments, learning media expert assessments, user (teacher) assessments, effectiveness tests based on observations of student activities, student response questionnaires, and learning outcomes tests. The research results show that based on expert assessment, the material is substantially correct there are no conceptual errors and the average in other aspects is 4.4, so the e-book is considered appropriate. Meanwhile, based on trials, it was obtained that student activity results reached an average of 94.3%, positive student responses reached 86.8% and student learning results reached 88.89%, so it can be concluded that e-books are considered effective in learning. Keywords: E-Book, Mathematica Logic, Moral Values, Pancasila Student Profile